2013
DOI: 10.2527/jas.2011-4949
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, diet nutrient digestibility, and bone mineralization in weaned pigs fed pelleted diets containing thermostable phytase1

Abstract: Traditional supplemental dietary phytase loses activity during steam pelleting. The thermal tolerance and bioefficacy of a phytase product with a thermoprotective coating [coated phytase (C-phytase)] was compared in mash and pelleted diets to a traditional, uncoated phytase (U-phytase) added to a negative control (NC) diet, formulated with reduced dietary Ca and P, and compared with a corn-soybean meal based positive control (POC) diet. Growth performance, nutrient digestibility, and third metacarpal bone char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 54 publications
(62 reference statements)
1
6
0
Order By: Relevance
“…As phytate-P cannot be hydrolyzed by mammalian enzymes (Cowieson et al, 2017), different strategies are applied to enhance the dietary P availability and consequently prevent P deficiencies in pigs, mainly dietary supplementation of phytase (Metzler-Zebeli et al, 2010) or (less frequently used) soaking and fermentation of cereals (Blaabjerg et al, 2011, 2012). However, the efficacy of exogenous phytase addition may be lower due to animal (e.g., gastrointestinal pH, digesta passage rate), and feed-related factors (e.g., dietary buffering capacity and pelleting temperature) (Blaabjerg et al, 2011, 2012; Kebreab et al, 2012; Yáñez et al, 2013). For this reason, feed-technological approaches (e.g., soaking and fermentation) that enhance the phytate-P availability in cereal grains prior to feeding to the animals have received more attention lately.…”
Section: Introductionmentioning
confidence: 99%
“…As phytate-P cannot be hydrolyzed by mammalian enzymes (Cowieson et al, 2017), different strategies are applied to enhance the dietary P availability and consequently prevent P deficiencies in pigs, mainly dietary supplementation of phytase (Metzler-Zebeli et al, 2010) or (less frequently used) soaking and fermentation of cereals (Blaabjerg et al, 2011, 2012). However, the efficacy of exogenous phytase addition may be lower due to animal (e.g., gastrointestinal pH, digesta passage rate), and feed-related factors (e.g., dietary buffering capacity and pelleting temperature) (Blaabjerg et al, 2011, 2012; Kebreab et al, 2012; Yáñez et al, 2013). For this reason, feed-technological approaches (e.g., soaking and fermentation) that enhance the phytate-P availability in cereal grains prior to feeding to the animals have received more attention lately.…”
Section: Introductionmentioning
confidence: 99%
“…However, adding appropriate carbohydrases has been shown to reduce the anti-nutrient effects of NSP in young pigs (Cadogan et al 2003;Zijlstra et al 2004;Kiarie et al 2007). It is also well documented that phytase supplementation to a P-deficient diet results in increased growth performance of pigs (Cromwell et al 1993;Han et al 1997;Yáñez et al 2014) and utilization of Ca and P (Adeola 1995;Olukosi et al 2007;Yáñez et al 2014). Carbohydrase addition to a diet high in NSP can lead to increased volatile fatty acid (VFA) concentration (Hübener et al 2002) and a reduction in ammonia production (Kiarie et al 2007), creating a condition that is favourable for the growth of beneficial bacteria, and inhibiting the proliferation of harmful or pathogenic bacteria in the gut (Pluske et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Phytase can not only breakdown phytate and increase the availability of phytate P, but also reduce the negative impacts of phytate on digestion of other nutrients such as amino acids and energy ( Selle et al., 2012 ). In weaned piglets, it has previously been reported that supplementation of an E. coli phytase increased ADG, apparent ileal digestibility of CP and amino acids compared with pigs fed a NC diet ( Yáñez et al., 2013 ). In other studies, using Buttiauxella phytase, it has been reported that supplementation with this enzyme improved energy and amino acids digestibility in piglets ( Zeng et al., 2015 ), grower pigs ( Adedokun et al., 2015 , Lizardo et al., 2015 ) and in broilers ( Amerah et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%